2020
DOI: 10.1017/s0954579420000036
|View full text |Cite
|
Sign up to set email alerts
|

Increased pupil dilation to happy faces in children with hyperactive/impulsive symptoms of ADHD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is associated with disrupted emotional processes including impaired regulation of approach behavior and positive affect, irritability, and anger. Enhanced reactivity to emotional cues may be an underlying process. Pupil dilation is an indirect index of arousal, modulated by the autonomic nervous system and activity in the locus coeruleus-noradrenergic system. In the current study, pupil dilation was recorded while 8- to 12- year old children (n = 71, 26 with a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…The first group (n = 39, mean age 12 years, SD = 2.64) was initially recruited from a database of families expressing interest in participating in developmental research and included as a control group in studies of ADHD. Details about the sample are reported in previous publications [47,48]. The second group (n = 41; mean age 14.28, SD = 2.43) were recruited from the Swedish tax registry (for details about the sample, see [35]) and initially included as a control group in a study on social anxiety disorder.…”
Section: Two Additional Infants Were Excluded Because Of a Lack Of Valid Data (See Data Processing)mentioning
confidence: 99%
“…The first group (n = 39, mean age 12 years, SD = 2.64) was initially recruited from a database of families expressing interest in participating in developmental research and included as a control group in studies of ADHD. Details about the sample are reported in previous publications [47,48]. The second group (n = 41; mean age 14.28, SD = 2.43) were recruited from the Swedish tax registry (for details about the sample, see [35]) and initially included as a control group in a study on social anxiety disorder.…”
Section: Two Additional Infants Were Excluded Because Of a Lack Of Valid Data (See Data Processing)mentioning
confidence: 99%
“…Groups were matched on age and gender (Table 1). The sample is partly overlapping with the group studied by Kleberg et al (2020), where data from another experiment are reported.…”
Section: Recruitment Of the Control Groupmentioning
confidence: 99%
“…Gaps in the data shorter than 150 ms were replaced through linear interpolation and subsequently filtered by a moving median filter corresponding to 80 ms. A pupil dilation response was calculated for each trial and defined as the mean proportional change in pupil size during stimulus presentation relative to baseline pupil size. As in previous studies (Kleberg, Frick, & Brocki, 2020;Kleberg et al, 2019), the initial increase in pupil size after stimulus onset that can largely be attributed to changes in screen luminance was discarded. Based on visual inspection of the data, pupil dilation response was defined as the mean pupil size during the 1500-4000 ms interval (see Supplementary materials, Figure S3).…”
Section: Recording and Processing Of Eye Tracking Datamentioning
confidence: 99%
See 2 more Smart Citations